2021
DOI: 10.3390/joitmc7010087
|View full text |Cite
|
Sign up to set email alerts
|

Women in Top Management: Performance of Firms and Open Innovation

Abstract: The lack of women’s presence in firms’ top management positions reflects gender equity problems, especially in South Asia, including Pakistan, and contours a firm’s financial behavior. Based on the underpinning of the conceptual framework developed by a combination of fourteen femininity theories, the current study investigates women’s induction in top management and its impact on a firm’s financial behavior. We collected data from annual reports of 60 non-financial firms listed at the Pakistan Stock Exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…Female CEOs also have a significant negative association with financial performance in small firms, while large firm performance has a positive and no significant effect on female CEOs. In the same vein Tahir, Ahmad, Syed, and Qadir [47] study also revealed a negative effect between Female CEOs and firm performance. This study considers Female CEOs to have women occupying the position of CEOs in the deposit money bank in Nigeria.…”
Section: Female Ceos and Firm Valuementioning
confidence: 66%
See 2 more Smart Citations
“…Female CEOs also have a significant negative association with financial performance in small firms, while large firm performance has a positive and no significant effect on female CEOs. In the same vein Tahir, Ahmad, Syed, and Qadir [47] study also revealed a negative effect between Female CEOs and firm performance. This study considers Female CEOs to have women occupying the position of CEOs in the deposit money bank in Nigeria.…”
Section: Female Ceos and Firm Valuementioning
confidence: 66%
“…Also, Ayman, Jalal, Mostafa and Irfan [5] in Kuwait studied the impact of Board Gender Diversity on Firm Value and discovered a positive and significant association between the female board of directors. The findings of this study support the conclusions of Satriyo and Harymawan [44]; and Tahir et.al., [47], which show a negative and significant link between Female CEOs and firm value, whereas the findings of Martin-ugedo, et al, [27]; and Dwlharti and Adhariani [10] in Spain and Indonesia show a positive and significant link between Female CEOs and firm performance. In Kenya, Gicheha and Muturi [13] found a negative and insignificant link between audit committee gender diversity and financial reports, supporting the findings of this study, whereas Mgbame, et al, [28]; and Omotoye, et al, [32] found a significant and positive link between audit committee gender diversity and market performance, contradicting the findings of this study.…”
Section: Gender Diversity and Earnings Per Share Of Listed Deposit Mo...mentioning
confidence: 78%
See 1 more Smart Citation
“…To examine female directors and corporate innovation spending of family firms, we specify the following multiple regression adopted by previous authors (Ain et al , 2021; Tahir et al , 2021): …”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Regarding the factors that facilitate women's access to managerial positions, Osi and Teng (2021) mentioned the influential and required factors on the professional success of women such as the drivers of professional success for women leaders and reflect the different levels of relationships and interactions women have in their organizations (mentors, colleagues, and subordinates) and families (husbands, sons, and fathers), which reflect cultural norms and standards such as myths and stereotypes, lack of training, discrimination (Osi and Teng, 2021;Tahir et al, 2021), machismo (Barrueto, 2021), lack of gender equality policies (Centrum, 2018) and workplace harassment (Pwc, WomenCEO Perú and IFC, 2021). The required factors could be commitment and greater momentum from the CEO and senior management (ILO, 2019), change of social paradigms (Barrueto, 2021), promotion of laws that consider their participation (Seierstad et al, 2017;Heller and Gabaldon, 2018) and female empowerment policies (Centrum, 2018;Brieger, 2019;Lewellyn, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%